Innovations in Artificial Intelligence for Surgery Assistance: Systematic Review of Applications and Clinical Efficacy - Quiliche Plasencia, Deysi Elvia Yuvixa (2025)
Artificial intelligence (AI) currently presents an innumerable number of implementations with widely proven results. Surgical assistance, a fundamental part of medical surgery, is a clear example of innovation and effective application of technologies that replicate different human qualities and skills to improve patient surgical care. The present research, through the PRISMA methodology, focuses on the analysis of AI applications for surgical assistance, making use of articles obtained after implementing a series of search, inclusion and exclusion criteria designed to achieve a total syntony between the scientific literature described and the central theme of the research. An in-depth search of the literature was performed in the ProQuest and Google Scholar databases and 18 articles were selected from a total of 272 candidates. The results show that technologies such as Machine Learning (ML), Deep Learning (DL), and Surgical Robotics are used to improve patient care with less invasive procedures and reduced risks. This study highlights the transformative impact of AI in surgical assistance and suggests the need for further research on its integration into new specialties, as well as ethical and regulatory aspects to ensure its safe use.